2014
DOI: 10.1021/ja411279r
|View full text |Cite
|
Sign up to set email alerts
|

Gear-Meshed Tiling of Surfaces with Molecular Pentagonal Stars

Abstract: The assembly of the chiral pentagonal-star-shaped 1,3,5,7,9-pentaphenylcorannulene on a Cu(111) surface has been studied with scanning tunneling microscopy. Two different long-range ordered phases coexist at 60 K, most likely racemic and homochiral phases. The principal motifs emulate a network of meshed gears. One of the observed structures resembles the densest packing of five-fold symmetric stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Bowl-shaped polycyclic aromatic hydrocarbons, also named buckybowls, have attracted interest due to their unique chemical and physical properties, [1][2][3][4] such as bowl inversion, [5,6] supramolecular assembly, [7,8] electronic conductivity, [9,10] and chirality. [11,12] In the past decade, C 3v -symmetric sumanene [13,14] and C 5v -symmetric corannulene, [2,3] as the typical subunits of C 60 , have been intensively investigated.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Bowl-shaped polycyclic aromatic hydrocarbons, also named buckybowls, have attracted interest due to their unique chemical and physical properties, [1][2][3][4] such as bowl inversion, [5,6] supramolecular assembly, [7,8] electronic conductivity, [9,10] and chirality. [11,12] In the past decade, C 3v -symmetric sumanene [13,14] and C 5v -symmetric corannulene, [2,3] as the typical subunits of C 60 , have been intensively investigated.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Other pioneering studies of liquid structure identified local fivefold symmetry, thus giving rise to the idea that it should have an important role in suppressing crystallization34. This concept of competition between fivefold symmetry in the liquid and sixfold crystalline symmetry underpins the design of materials as diverse as metallic glasses56, quantum liquids7, pentagonal molecules8 and colloidal polymers9.…”
mentioning
confidence: 99%
“…As mentioned above, the tiling of a flat surface with other C 5 corannulene molecules resulted in hexagonal arrays of those pentagonal star‐shaped molecules,, not pentagonal arrays of pentagons as in the ab planes in CORA‐5‐1 . Pentagonal arrays of objects of any shape, even molecules or supramolecular assemblages of molecules with fivefold or pseudo‐fivefold symmetry, are not commonly found in two‐ or three‐dimensional crystals because, as is well known, pentagonal arrays cannot tile space effectively .…”
Section: Resultsmentioning
confidence: 92%